The dilemma of popular sovereignty in the Middle East power from or to the people? - Chatterjee, Kingshuk; Singh, Priya (Institute of Foreign Policy Studies, Centre for Pakistan and West Asian Studies, Calcutta University in association with KW Publishers, New Delhi, 2014)
The ongoing political turmoil in the Middle East as a whole would seem to be essentially a contest between the minimalist and maximalist positions on popular sovereignty: should power merely come from, and be exercised in the name of, the people? Or, should those in power be fully accountable to the people? The dilemma warrants a closer look. The present volume comes out of an international conference held in Calcutta, India organised by the Institute of Foreign Policy Studies and the Centre for Pakistan and West Asian Studies, University of Calcutta in March 2013. This volume aims not at a definitive analysis of why what happened did happen; it aims instead at getting a sense of what was actually happening, and what is at issue